The Relationship between Emotional Intelligence, Foreign Language Anxiety, and Demotivational Factors in an English Preparatory Language Program - Mede, Enisa; Budak, Tugce (Colombian Applied Linguistics Journal, 2021)
This study aims to investigate the relationship between emotional intelligence (EI), foreign language anxiety (FLA), and demotivational factors (DF) at a foundation university in Istanbul, Turkey. 148 B1 (intermediate level) students enrolled in the English preparatory school participated in this study. Data were collected from the Turkish-adapted version of the Emotional Intelligence Quotient Inventory (EQ-i), the translated version of the Foreign Language Classroom Anxiety Scale (FLCAS), and the Turkish preparatory school university student demotivational factors towards learning English scale. The findings revealed that the participants were moderately anxious and demotivated in foreign language learning. Moreover, a positive significant correlation was found among EI, FLA, and DF. This study provides pedagogical implications and suggestions for addressing EI, FLA, and DF in English language preparatory programs.